Quantifying spatial association between mineral deposits and geology across three African crustal segments of different age, with implication for secular change in mineralization during earth history - Mabidi, Tshifhiwa (Department of Geological Sciences, 2016)
Variations in enrichment of mineralization, expressed in ore deposits, in the continental crust may be one way to test for secular changes in crustal genesis. This study collates and analyses fundamental information about mineral deposits with which to 'fingerprint' the metal endowment of African crust of different age. Three areas of juvenile African crust (e.g. mantle derived over similar lengths of time of ~500 million years, and excluding recycled older crust) of different ages with similar geology are compared. The areas range in age from 0.5 to 3.0 Ga, [e.g. the Zimbabwe Craton (2.5-3.0 Ga), the Birimian Shield (1.8-2.3 Ga), and the Arabian-Nubian Shield (0.5-1.0 Ga)]. The three areas have a total of 2671 mineral deposits, which are divided into six groups according to their geochemical affinities. Using these known deposits, mineral potential maps are created through a data driven approach, using weights of evidence (WotE). The layers/themes used in Woffi are (1) lithology, (2) structures (faults and shear zones), and (3) lithological contacts. The analysis shows that there is strong lithology control on mineralization in all three areas. Archean crust has high predictive values compared to the younger crust. A measure of spatial association (spatial coefficient), based on the WotE approach, is also used to 'fingerprint' the met I endowment in the three selected regions of African crust. The patterns of the mineral deposits distribution within all regions shows that each region has a unique metal endowment, and that there is a greater concentration of mineral deposits in the crust of the Archean Zimbabwe Craton relative to the younger crust of the Birimian and Arabian-Nubian Shields. The analysis of this study therefore quantitatively corroborates studies that suggest older crust is more mineral diverse and more enriched in mineral deposits than younger crust. Thus, secular changes in mineralization or rates of tectonic processes, or both, are implicated, and mineral endowment in the African crust has undergone major evolutionary changes from Archean to Neoproterozoic time.